«Kazakhstan backround and National Brand» (Журналистика сериясы, 2016)
In this year we will celebrate 25th anniversary of Independence of Ka-zakhstan Located in the center of Eurasia, Kazakhstan was at the crossroads of ancient civilizations of the world, at the crossroads of transport routes, social and economic, cultural and ideological relations between East and West, North and South, between Europe and Asia. This article discusses the concept of branding and сountry branding. “Country branding” is largely determines the level of investment and tourist attractiveness of countries seriously affected by the popularity of the goods produced by them on the international scene, and even a place in the global division of labor. This research will study Kazakhstan’s use of mediated public diplomacy to de-fine its national identity and improve the country’s image abroad. Today, having a good international reputation and a positive country brand is an integral part of a nation’s image, both inside the country and abroad.